A Boundary Adaptive Neural Network Coverage Path Planning Algorithm for Maritime Search and Rescue With AUVs Based on Target Drift Prediction - Zhou, Nan; Zhu, Zhongben; Qin, Hongde; Zhou, Lin; Bai, Guiqiang; Xue, Yifan; Mu, Xiaokai (Journal of field robotics, 2025)
The development of maritime trade and operations has led to a gradual increase in maritime accidents. Research on the specificity of maritime search and rescue (SAR) missions is essential to improve mission efficiency; however, traditional SAR programs usually use predefined paths to conduct searches, which is difficult to meet the timeliness and uncertainty requirements. To solve the challenge, we propose a Boundary Adaptive Neural Network Coverage Path Planning Scheme based on Target Drift Prediction (BANCP‐TDP). The framework includes three modules: drift trajectory prediction, optimal region determination, and coverage search. First, the Limited Red‐billed Blue Magpie Optimizer Back Propagation drift model is used to predict the drift trajectory of the wrecked target. Subsequently, we use the Multiphysics Monte Carlo Gravitational Search prediction model to determine the distribution of targets at different moments and the optimal SAR region for guiding an autonomous underwater vehicle to carry out SAR missions. Then, we propose a BANCP for the SAR regions with complex boundaries, aiming to minimize the path length and maximize the coverage ratio. The comparative field experiments at Qingdao Jin Cao Gou reservoir and simulation results show that the proposed framework can effectively shorten path length while minimizing the repeated paths.